Efficacy of microwave ablation for the treatment of endometrial carcinoma: A report of 3 cases - NAKAMURA, KOHEI (Oncol Lett, 2016)
Microwave endometrial ablation (MEA) is effective for the emergency control of uterine hemorrhage. However, to the best of our knowledge, there has been only a single report of life-threatening hemorrhage induced by endometrial carcinoma that was treated with MEA. The present report evaluates the efficacy of MEA as an emergency therapeutic option for the control of bleeding due to advanced endometrial carcinoma and minimally-invasive, early-stage endometrial carcinoma in 3 patients. MEA was able to effectively control massive uterine bleeding due to endometrial carcinoma in 2 patients with advanced disease and was curative in a patient with minimally-invasive endometrial carcinoma. Given its safety, simplicity and effectiveness, MEA may be utilized for the emergency treatment of uterine bleeding in advanced endometrial carcinoma, and may be used as a curative treatment in early-stage endometrial carcinoma.